OOK Modulation Using intelligent OMIC Less Power Aware Clocked Threshold Inverter Quantized Flash ADC - Brundavani, P.; Vardhan, D. Vishnu (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Because it connects the analog physical world and the digital logical world, an analog-to-digital converter, also known as an ADC, is a fundamental component of system-on-chip (SoC) products. System-on-a-chip (SoC) uses of CMOS flash ADCs benefit from threshold inverter quantization (TIQ). TIQ is a method that use a voltage comparator built from two cascaded CMOS inverters. The recent developments in SoC design need the development of this TIQ technique to accommodate the increased integration of ADCs with other electrical circuits on the chip and the increased emphasis on low-power and low-voltage uses. This idea addresses the need for an analog-to-digital (ADC) converter that is both efficient and upgraded for the coherent detection of On-Off Keying (OOK) methods. A modulation strategy known as on-off keying, or OOK, involves turning on and off a sinusoidal carrier signal with a unipolar binary signal. This is done in order to create a modulated signal. OOK is analogous to the amplitude-shift keying (ASK) technique that uses two levels. OOK modulator If there is a zero to transmit, the RF carrier should simply be turned off, and if there is a one, the carrier should be sent at full power. The ADC design technique is cutting edge; it does away with the resistor ladder entirely, which brings about a significant reduction in the power demand of an analog to digital converter.